Initial Symptoms of Langerhans Cell Histiocytosis: A Case Series - Yukari Atsumi MD; Yuya Saito MD; Hiroshi Hataya MD; Yuki Yuza MD (SAGE Publishing, 2019)
Langerhans cell histiocytosis (LCH) is a rare childhood hematopoietic disease, and hence, there are few reports summarizing the course leading to the diagnosis. We described the initial symptoms and the clinical course of LCH. We carried out a retrospective review of charts from a single medical center, and 21 patients with the diagnosis of LCH were enrolled. The initial symptoms of 16 cases were caused by bone lesions; of these cases, there were 8 instances of soft tissue swelling as the initial symptom (38%) and 8 instances of bone pain without swelling (38%). Among the cases of bone lesion, 4 of 6 cases of skull lesion were painless while all vertebral body lesions and long bone lesions were accompanied by pain. LCH bone lesions caused various symptoms depending on the site of the lesion and this makes the diagnosis difficult. A detailed physical examination and imaging studies are recommended for early diagnosis.